Israel : Financial System Stability Assessment. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This paper discusses the Financial System Stability Assessment of Israel. The stability analysis suggests that systemic financial vulnerabilities to severe shocks in line with historical experience are manageable and in aggregate, buffers are at comparatively comfortable levels. The authorities already operate an effective, proactive, and sophisticated system of financial sector oversight, which, however, needs to be developed further in some areas. The authorities have underpinned the functioning of the financial system by enhancing the central bank liquidity framework and introducing a real-time gross settlement system.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet